Feasibility of piezoceramic transducer-enabled active sensing for the monitoring cross-shaped concrete filled steel tubular (CCFST) columns under cyclic loading - Zhai, Quan; Zhang, Jicheng; Xiao, Jiahao; Du, Guofeng; Huang, Yongshui (Measurement : journal of the International Measurement Confederation, 2021)
•The low-frequency cyclic loading test of CCFST columns is implemented.•An active sensing method based on piezoelectric sensor is applied in CCFST columns.•It’s verified that piezoelectric sensor can be used to monitor concrete damage. Cross-shaped concrete-filled steel tubular (CCFST) columns are used extensively in many infrastructural systems; however, the damage inside CCFST columns is difficult to inspect or monitor. This study develops a method based on embedded smart aggregates (SA) to monitor damage sustained by the concrete inside the CCFST column under low-frequency cyclic loading. Three CCFST columns with different width and wall thicknesses were fabricated and used as subjects to monitor the damage of the internal concrete using embedded piezoelectric SAs. Then, the measured piezoelectric signal undergoes wavelet packet analysis in order to be represented by a damage index (DI). The experimental outs show that the damage indices of the structure when exposed to low-frequency cyclic loading is basically consistent with the hysteretic and skeleton curves of the tested specimens, and is basically consistent with the observed experimental behavior. Overall, the results demonstrate the effectiveness of SAs in monitoring the formation of damage in the concrete inside CCFST.